2021
DOI: 10.1002/ana.26060
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Abnormalities are Common inCOVID‐19 and are Associated with Outcomes

Abstract: The aim was to determine the prevalence and risk factors for electrographic seizures and other electroencephalographic (EEG) patterns in patients with Coronavirus disease 2019 (COVID-19) undergoing clinically indicated continuous electroencephalogram (cEEG) monitoring and to assess whether EEG findings are associated with outcomes. Methods: We identified 197 patients with COVID-19 referred for cEEG at 9 participating centers. Medical records and EEG reports were reviewed retrospectively to determine the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…Due to infection control measures present at the time of the study, further neuroimaging and EEG studies were limited and generally not available for this report. This raises the question of underestimating the burden of neurology morbidity [29] , although the presence or absence of ongoing neuronal injury may be accurately assessed with NfL [30] . In addition, the wasting of peripheral nerves, a recognized feature in ICU patients, may contribute to increased NfL concentrations, although it cannot explain an increase in GFAp [31] , [32] , [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to infection control measures present at the time of the study, further neuroimaging and EEG studies were limited and generally not available for this report. This raises the question of underestimating the burden of neurology morbidity [29] , although the presence or absence of ongoing neuronal injury may be accurately assessed with NfL [30] . In addition, the wasting of peripheral nerves, a recognized feature in ICU patients, may contribute to increased NfL concentrations, although it cannot explain an increase in GFAp [31] , [32] , [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to infection control measures present at the time of the study, further neuroimaging and EEG studies were limited and generally not available for this report. This raises the question of underestimating the burden of neurology morbidity [29] , although the presence or absence of ongoing neuronal injury may be accurately assessed with NfL [30] . In addition, the wasting of peripheral nerves, a recognized feature in ICU patients, may contribute to increased NfL concentrations, although it cannot explain an increase in GFAp [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, detection of isolated electrographic seizures without preceding or following clinical seizures is exceptionally rare [25,26]. However, a more recent review by Lin et al reported that up to 4% of clinically ill patients may have evidence of non-convulsive status epilepticus in EEG without associated clinical seizures, which highlights both the importance and underutilization of EEG in critically sick COVID-19 patients [27]. Of note, despite the presence of an overall 1% incidence of acute symptomatic seizures as a part of COVID-19 infection symptomatology, the incidence of short and long-term epilepsy in those patients is not yet known [28].…”
Section: Discussionmentioning
confidence: 99%